The Impact of Digital Addiction on Technology-Related Fatigue among University Preservice Teachers in Ghana: Digital Addiction on Technology-Related Fatigue Among University Preservice Teachers In Ghana (Journal of Science and Technology, 2025)
In digitally connected environments, users of digital technologies and applications need to pay persistent attention to the overwhelming demands of their use. These expanded energy conditions may induce technology-related fatigue, leading to a physical and mental imbalance in the availability of the inner resources needed to perform certain tasks. In this study, we analysed the effects of subtypes of digital addiction (smartphone addiction, social media addiction, internet gaming disorder, and problematic internet use) on technology-related fatigue among university preservice teachers in Ghana. Employing a descriptive correlational design, data were collected from 220 preservice teachers at a public university in Ghana. Data were garnered employing the sociodemographic traits, psychometric scales that measure the subtypes of digital addiction and the Piper Fatigue Scale. Bivariate correlation (Pearson’s r) and multivariate regression analysis were used to analyse the relationship between the digital addiction subtypes and technology- related fatigue. The results illustrated that the subtypes of digital addiction explained 27.9% (R2=0.279) of the total variance in fatigue levels. Smartphone addiction was the most important factor associated with technology-related fatigue. Notably, this study is among the first to empirically establish a statistically significant relationship between digital addiction subtypes and TRF in the context of higher education in Sub-Saharan Africa. The findings underscore the need for awareness campaigns and targeted interventions within teacher education programmes to mitigate the adverse health impacts of digital overuse.